2020
DOI: 10.1038/s41467-020-16142-7
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination DNA repair deficiency and PARP inhibition activity in primary triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) encompasses molecularly different subgroups, with a subgroup harboring evidence of defective homologous recombination (HR) DNA repair. Here, within a phase 2 window clinical trial, RIO trial (EudraCT 2014-003319-12), we investigate the activity of PARP inhibitors in 43 patients with untreated TNBC. The primary end point, decreased Ki67, occured in 12% of TNBC. In secondary end point analyses, HR deficiency was identified in 69% of TNBC with the mutational-signature-based HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
153
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 55 publications
9
153
0
Order By: Relevance
“…We found that a majority ( n = 8) of 12 patients with gHRRm had HRD-high tumors consistent with previous reports [ 4 , 7 , 8 , 10 , 11 , 21 , [32] , [33] , [34] , [35] , [36] ]. These eight patients had BRCA1 or BRCA2 germline mutations.…”
Section: Discussionsupporting
confidence: 92%
“…We found that a majority ( n = 8) of 12 patients with gHRRm had HRD-high tumors consistent with previous reports [ 4 , 7 , 8 , 10 , 11 , 21 , [32] , [33] , [34] , [35] , [36] ]. These eight patients had BRCA1 or BRCA2 germline mutations.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, different genomic signatures for HRD or BRCAness have been tested as potential predictive markers for platinum or PARP inhibitor sensitivity, revealing conflicting results. 12,26,36,42 Here, 69% of TNBC harbored a basal-like subtype by PAM50 analysis, but the basal-like subtype was not enriched among olaparib responders. Also, using MLPA analysis, we found the BRCA1-like signature not to be predictive of response to olaparib in the current patient cohort.…”
Section: Discussionmentioning
confidence: 87%
“…Our results thus indicate that a large number of patients who would potentially benefit from PARPi therapy still remain unnoticed. Since the mutational phenotype of HRD is independent of cancer type, mutational scar based HRD detection such as with CHORD would be valuable for cancer type agnostic patient stratification for future PARPi trials 31 . This is particularly important for metastatic patients (who depend on systemic treatments and benefit most from targeted treatments like PARPi), as well as for cancer types currently lacking good markers for patient stratification for such treatment (such as prostate 32 and biliary 33 cancer).…”
Section: Discussionmentioning
confidence: 99%